Programmes of the International Livestock Research Institute and their impact on human health - Smalley, M.E. (Swedish University of Agricultural Sciences, 1996)
The International Livestock Research Institute (ILRI) has been established to improve animal agriculture in developing countries through research and research-related programmes. The successful implementation of the Institute's programme will improve the welfare of rural and urban communities in developing countries. However, there are projects within the ILRI research programme that have an immediate impact on human health. ILRI's research on Theileria parva, the causative agent of East Coast fever, has shed new light on the processes involved in cell transformation. T. parva induces lymphoblastogenesis in its host. The role of the enzyme casein kinase II in this proliferative process has led to new discoveries about how human tumours may develop. New research by ILRI on peri-urban dairying will investigate if and how the adoption of crossbred cows can increase farm income and result in improved household health and nutrition. The research, in Ethiopia, is exploring the link between increased milk production and the consumption of macro- and micronutrients necessary for growth and proper physical and mental Development. ILRI's work to model the transmission and host-parasite interactions of trypanosomiasis and East Coast fever contributes to understanding the epidemiology of these diseases. The work has wider relevance for other infectious diseases, including those of man. Finally the paper describes ILRI's work showing that human nutritional status may be used as reliable non-economic indicators of the effects of improving control over animal diseases. The paper concludes by highlighting the possible interactions between research to improve animal health and production, and that to improve human health and nutrition.